SOME HAEMATOLOGICAL VALUES IN NORMAL DOGS - Saleem Amin Hasso; Rahman Kadhum Muhsen (Basrah Journal of Veterinary Research)
Haematological values of sixty normal dogs aged from 2 months to 2 years of both sexes were estimated. Red blood cells count (RBCs), hemoglobin concentration (Hb), packed cell volume (PCV). Mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), total and differential leukocyte count, total plasma protein, plasma albumin, fibrinogen and globulins were determined using several laboratory techniques and equations. The results revealed that, all RBCs parameters decreased with age except Hb, MCH and MCHC. The latter two increased with age while Hb was unchanged. All other parameters increased significantly with age. There were no significant differences in all parameters between both sexes.